Analysis of Variables Affecting Reference Block Equivalency Process Using Ndt Ultrasonic Method - Rizka Natasya Maharani; Alaya Fadllu Hadi Mukhmad; Wiji Mangestiyono; Sutrisno; Ghifar Maulana (Engineering Proceedings)
Non-destructive testing (NDT) aims to assess components without compromising their functionality by identifying internal defects. Ultrasonic testing, a key NDT method, uses sound waves (0.5–20 MHz) to detect imperfections and requires tool calibration with reference blocks for accuracy. This study focuses on ultrasonic techniques and the equivalence of tool calibration and parameter adjustments. It involves selecting a reference block for testing and comparing it to a standard reference. The ultrasonic instrument checks if the alternate block produces a signal equivalent to the standard. Results showed a full screen length (FSL) difference, highlighting factors affecting reference block equivalence.